2013
DOI: 10.1186/1479-5876-11-288
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-12 contributes to tumorigenicity in colorectal cancer by promoting migration, invasion, adhersion and angiogenesis

Abstract: BackgroundCadherin 12 (CDH12), which encodes a type II classical cadherin from the cadherin superfamily, may mediate calcium-dependent cell adhesion. It has been demonstrated that CDH12 could play an important role in the invasion and metastasis of salivary adenoid cystic carcinoma. We decided to investigate the relationship between CDH12 expression level and clinicopathologic variables in colorectal carcinoma (CRC) patients and to explore the functions of CDH12 in tumorigenesis in CRC.MethodsThe expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…The upregulation of CDH12 protein following DMH administration with the development of ACF is consistent with the fact that CDH12 promotes proliferation and tumorigenesis [46,47]. This In support, SOX7 over-expression suppressed cell proliferation and colony formation in prostate and CRC cell lines and induced apoptosis in CRC cells [49,50].…”
Section: Combination Treatment With Qu and 5-fu Was Associated With Dsupporting
confidence: 57%
“…The upregulation of CDH12 protein following DMH administration with the development of ACF is consistent with the fact that CDH12 promotes proliferation and tumorigenesis [46,47]. This In support, SOX7 over-expression suppressed cell proliferation and colony formation in prostate and CRC cell lines and induced apoptosis in CRC cells [49,50].…”
Section: Combination Treatment With Qu and 5-fu Was Associated With Dsupporting
confidence: 57%
“…When cancer cells escape from the primary site to metastasis, subsets of cancer cells undergo a morphological conversion from an epithelial-like phenotype to a mesenchyme-like phenotype [25]. This process is characterized by the loss of epithelial cell junction proteins, such as E-cadherin, and an upregulation of mesenchymal markers, such as Vimentin and N-cadherin [26]. In this study, we found that CRC cells with high levels of CXCL5 expressed low levels of E-cadherin and ZO-1 and high levels of N-cadherin and Vimentin.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described [35]. 100 ug of protein was separated by 10% SDS-PAGE gel and transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%